2011
DOI: 10.1542/peds.2010-2046
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-Smoke Exposure in Children Who Live in Multiunit Housing

Abstract: Most children without known secondhand tobacco-smoke exposure inside the home still showed evidence of tobacco-smoke exposure. Children in apartments had higher mean cotinine levels than children in detached houses. Potential causes for this result could be seepage through walls or shared ventilation systems. Smoking bans in multiunit housing may reduce children's exposure to tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 28 publications
3
119
5
2
Order By: Relevance
“…A systematic review and meta-analysis of the effectiveness of interventions to reduce ETS in homes as assessed by reduction in nicotine and PM levels found that although some benefits were documented, at follow-up, exposure was still present [114]. ETS exposure, as measured by cotinine levels, was consistently higher in children who lived in multiunit or attached housing compared to children living in detached homes, even if there were no smokers within the home [115]. Regulations to enforce smoke-free multiunit housing is a feasible intervention, particularly for new developments [114,116] that should be considered in LMIC regions, especially where government-subsidized housing may be provided.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review and meta-analysis of the effectiveness of interventions to reduce ETS in homes as assessed by reduction in nicotine and PM levels found that although some benefits were documented, at follow-up, exposure was still present [114]. ETS exposure, as measured by cotinine levels, was consistently higher in children who lived in multiunit or attached housing compared to children living in detached homes, even if there were no smokers within the home [115]. Regulations to enforce smoke-free multiunit housing is a feasible intervention, particularly for new developments [114,116] that should be considered in LMIC regions, especially where government-subsidized housing may be provided.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking in one unit involuntarily exposes those in nearby units. 5,75,76 Besides protecting the health of the children, prohibitions on smoking protects their investment from damage by tobacco smoke and tobacco smoking caused fires.…”
Section: Smoking In Multi-unit Housingmentioning
confidence: 99%
“…27 Visits to PROS practices are comparable to national office visit data from the National Ambulatory Medical Care Survey. 26,28 For this study, we invited the participationofallPROSpracticesthat(1) included at least 3 practitioners, (2) were not housed within a medical school or parent university, (3) saw at least 50 patients per day, and (4) saw at least 10 patients per day with 1 or more parent smokers. The first 22 practices that responded were enrolled and randomly assigned to intervention orcontrol groups.…”
Section: Samplementioning
confidence: 99%
“…Quitting smoking adds an average of 7 years to a parent' s life, 1 eliminates most of their children' s tobacco smoke exposure (TSE), [2][3][4] eliminates smoking-related poor pregnancy outcomes for all future pregnancies, 5 addresses the primary cause of house fire mortality, 6,7 decreases the accessibility of cigarettes and odds that teens become smokers, [8][9][10] and improves the financial resources of disadvantaged families. 11 Therefore, helping parents quit smoking is a critically important national priority.…”
mentioning
confidence: 99%